HUBUNGAN PEMBERIAN PMT DENGAN PERUBAHAN STATUS GIZI PADA IBU HAMIL DENGAN KEK DI PUSKESMAS KARANGGEDE - Setyawati, Dwi; Yuliastanti, Triani; Wijayanti, Titik (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2026)
Background. Efforts to improve the nutrition of pregnant women with KEK involve the provision of supplementary food. According to Ministry of Health Regulation No. 51 of 2016 on Standards for Nutritional Supplementation Products for the Provision of Supplementary Food (PMT) to Pregnant Women. The objective of this study was to determine the relationship between the provision of PMT and changes in nutritional status among pregnant women with KEK at the Karanggede Community Health Center. Methods. This was a quantitative study using an analytical survey design, specifically a case-control study. The study population consisted of all pregnant women with KEK at the Karanggede Community Health Center from January to December 2025, totaling 97 pregnant women. The sample in this study consisted of 30 pregnant women with KEK who received PMT in 2025, plus 30 pregnant women with KEK who did not receive PMT in 2025. In this study, 30 of the 67 pregnant women with KEK who did not receive PMT were selected at random. All pregnant women with KEK who received PMT were included. Data analysis was performed using the chi-square test. Research findings. The nutritional status of pregnant women with KEK at the Karanggede Community Health Center improved in the majority of cases, with 48 respondents (80.0%) showing an improvement. There is an association between the PMT intervention and changes in nutritional status among pregnant women with KEK at the Karanggede Public Health Center in Boyolali (p-value 0.010), with an OR of 7, meaning that PMT administration improves the nutritional status (BMI) of pregnant women 7 times more than in pregnant women with KEK who did not receive PMT Conclusion. There is an association between the PMT intervention and changes in nutritional status among pregnant women with KEK at the Karanggede Community Health Center in Boyolali. The research results are used as input to facilitate education on the importance of nutritional status in pregnant women, starting from preconception preparation. Keywords: Intervention, Supplementary feeding, KEK, nutritional status, BMI